2022
DOI: 10.9734/ajrcs/2022/v7i330143
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Some Plant Mulches and Tomato Cultivars on the Growth Parameters and Wilt of Tomato (Lycopersicon esculentum Mill) in Owerri, Imo State, South East, Nigeria

Abstract: The experiment was conducted on the effects of some mulching materials and some tomato cultivars on the growth parameters and wilt disease of tomato. The design used was 3 x 4 factorial in Randomized Complete Block Design (RCBD), in four (4) replications. The work was carried out in 2015 cropping seasona at the Teaching and Research Farm of the School of Agriculture and Agricultural Technology, Federal University of Technology, Owerri, Imo State, Nigeria.  on growth parameters and disease incidence on tomato w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The average temperature is 26.4 o C [18]. The geographical coordinates of the study area are 5.4891 0 N and 7.025853E [19]. Analysis of variance indicated that aqueous extract of neem seed application significantly (P<0.05) led to the production of the tallest Pigeon pea plant (103.30 cm), the highest number of pigeon pea leaves (99.40), the lowest phytophthora blight disease incidence (11.00%) and also the lowest phytophthora blight disease severity (1.00).…”
Section: Description Of the Experimental Sitementioning
confidence: 99%
“…The average temperature is 26.4 o C [18]. The geographical coordinates of the study area are 5.4891 0 N and 7.025853E [19]. Analysis of variance indicated that aqueous extract of neem seed application significantly (P<0.05) led to the production of the tallest Pigeon pea plant (103.30 cm), the highest number of pigeon pea leaves (99.40), the lowest phytophthora blight disease incidence (11.00%) and also the lowest phytophthora blight disease severity (1.00).…”
Section: Description Of the Experimental Sitementioning
confidence: 99%